Inactivation of Pseudomonas aeruginosa in mineral water by DP1 bacteriophage immobilized on ethylene‐vinyl acetate copolymer used as seal caps of plastic bottles. Issue 35 (6th February 2020) - Novello, Júnia; Sillankorva, Sanna; Pires, Priscila; Azeredo, Joana; Wanke, César Henrique; Tondo, Eduardo César; Bianchi, Otávio
Abstract: Pseudomonas aeruginosa has been found in bottled natural mineral water, even though its presence is not allowed in this product by different food regulations. This study aimed to investigate the inactivation of P. aeruginosa present in mineral water by vB_PaeM_CEB_DP1 (short name DP1) bacteriophage immobilized on ethylene‐vinyl acetate (EVA) copolymer used as seal caps of plastic bottles. EVA was chemically modified using microwave‐assisted alcoholysis, improving polymer‐phage binding. After that, DP1 phage was attached to EVA and EVA‐OH copolymers and both surfaces were tested for plaque formation using P. aeruginosa. Then, both materials containing immobilized phages were used as seal caps of plastic bottles and its antimicrobial capacity was tested against P. aeruginosa contaminating mineral water. The EVA‐OH resulted in higher hydrogen bond density that contributed significantly to the phage immobilization on the polymer surface. The polymers containing immobilized phages were able to reduce 0.53 log of P. aeruginosa population present inside mineral water bottles after 14 days. Abstract :